Effect of air humidification on the sick building syndrome and perceived indoor air quality in hospitals: a four month longitudinal study. - Nordström, K (1994)
The sensation of dryness and irritation is essential in the sick building syndrome (SBS), and such symptoms are common in both office and hospital employees. In Scandinavia, the indoor relative humidity in well ventilated buildings is usually in the range 10-35% in winter. The aim of this study was to evaluate the effect of steam air humidification on SBS and perceived air quality during the heating season. The study base consisted of a dynamic population of 104 hospital employees, working in four new and well ventilated geriatric hospital units in southern Sweden. Air humidification raised the relative air humidity to 40-45% in two units during a four months period, whereas the other two units served as controls with relative humidity from 25-35%. Symptoms and perceived indoor air quality were measured before and after the study period by a standardised self administered questionnaire. The technical measurements comprised room temperature, air humidity, static electricity, exhaust air flow, aerosols, microorganisms, and volatile organic compounds in the air. The most pronounced effect of the humidification was a significant decrease of the sensation of air dryness, static electricity, and airway symptoms. After four months of air humidification during the heating season, 24% reported a weekly sensation of dryness in humidified units, compared with 73% in controls. No significant changes in symptoms of SBS or perceived air quality over time were found in the control group. The room temperature in all units was between 21-23 degrees C, and no significant effect of air humidification on the air concentration of aerosols or volatile organic compounds was found. No growth of microorganisms was found in the supply air ducts, and no legionella bacteria were found in the supply water of the humidifier. Air humidification, however, significantly reduced the measured personal exposure to static electricity. It is concluded that air humidification during the heating season in colder climates can decrease symptoms of SBS and perception of dry air.